An Exact Analytical Solution of the Strong Shock Wave Problem in Nonideal Magnetogasdynamics. (21st October 2013) - Ram, S. D.; Singh, R.; Singh, L. P.
Abstract : We construct the solutions to the strong shock wave problem with generalized geometries in nonideal magnetogasdynamics. Here, it is assumed that the density ahead of the shock front varies according to a power of distance from the source of the disturbance. Also, an analytical expression for the total energy carried by the wave motion in nonideal medium under the influence of magnetic field is derived.